Holistic Learning Model Increase Asetilkoline Level and Caring Behavior on Student in Caring Patiens with Ischemic Stroke - Luluk Widarti; Siti Maimuna; Tanty Wulandari; Moch Bahrudin (Universitas Airlangga, 2014)
Introduction: Holistic learning requires attention and potential of students that covers aspects of intellectual, emotional, physical, artistic, spiritual, and creativity.Methods: This study used a pre-experimental design. The samples in this study were 30 students in semester 2 of nursing diploma Sidoarjo. Samples given intervention in the form of holistic learning, and given a pretest and posttest including measurement of acetylcholine levels by quantitative Elisa technique, and caring behavior by using questionnaires and observations. Data were analyzed using levene’s test, t-test, wilcoxon test and correlation.Results: Statistical analysis showed that there was significant difference in the level of asetilkoline before and after the intervention with p = 0.015, whereas significant differences in caring behavior indicates p = 0.001. The result of correlation test showed that there was significant correlation between the levels of acetylcholine and caring behavior after intervention (r = 0.003).Disscussion: It was concluded that the holistic learning model can improve the asetilkoline levels and caring behavior of the students. Lecturers are encouraged to use the model of holistic learning in teaching students.